Peran Self Efficacy sebagai Mediator dalam Hubungan antara Implementasi Moderasi Beragama dan Pembentukan Karakter Siswa MA Islamiyah Senori - Maftuhah, Siti (Madrasah Ibtidaiyah Education Journal, 2025)
This research aims to determine the role of self-efficacy as a mediator in the relationship between the implementation of religious moderation and the character formation of students at Islamiyah Islamic Senior High School Senori. This study uses a quantitative approach with an ex-post facto design. The sampling technique uses the Proportionate Stratified Random Sampling technique. The sample was taken from class XI of Islamiyah Islamic Senior High School, Senori. The data analysis technique used is the SEM-PLS technique using the SmartPLS 4 application. The results of this study include the implementation of religious moderation having a significant effect on the formation of student character, with a p-value of 0.000. Self efficacy has a significant effect on the formation of student character, with a p value of 0.047. Self efficacy has a significant effect on the implementation of student religious moderation, with a p-value of 0.000. Self efficacy has a role as a mediator in the relationship between the implementation of religious moderation and the formation of student character, with a p-value of 0.000